Perencanaan Perawatan Mesin Pump 107 Dengan Metode Reability Centered Maintenance (RCM) di PT. Petrokimia Gresik - Rezza Wira Utomo (Jurnal Energi dan Teknologi Manufaktur, 2018)
PT. Petrokimia Gresik is one of the largest fertilizer companies in Indonesia, locatedin Gresik, East Java. The pump 107 engine on the Ammonia unit is often damaged due to itslargest size compared to other types of pumps, as well as the result of carrying thick orconcentrated fluid (bluish black) so that it is heavy for the drainage process. The purpose ofthis study is to plan and recommend the proposed treatment method on the pump enginebased on the method used to improve the working efficiency of the pumping machine 107and determine the failure mode and diagnosis of the effects of failure modes that occur in thecomponent. The method used is the Reability Centered Maintenance (RCM) method whichis expected to be able to produce maintenance or maintenance scheduling that is increasinglydirected so that it can improve the performance and efficiency of the engine, reduce repaircosts, and extend the service life of the machine itself. From this study, the results are in theform of Faliure Model And Effect Analysis (FMEA), FMEA table preparation is carried outbased on component function data and maintenance reports which can then be determined byvarious failures resulting in malfunction. From the compilation of FMEA, it can be seenwhat the causes of failure are and what impacts they have caused. Next, the value of MeanTime Between Failure (MTBF) pump 107-JA is 15,829 hours, pump 107-JB is 43,764 hoursand pump 107-JCM is 19,578 hours. Maintainability M (t) or Mean Time to Repair (MTTR)value on pump 107-JA is 2,914 hours, pump 107-JB is 3,411 hours, and pump 107-JCM is3,1 hours, Availability A (t) value is pump 107-JA at 84.44%, pump 107-JB at 92.76% andpump 107-JCM at 86.31%. The last one is found that the failure rate of pump 107-JA is0.063172, pump 107-JB is 0.02284 and pump 107-JCM is 0.051.